Anti-phosphatidylserine/prothrombin antibodies and thrombosis associate positively with HLA-DRB1*13 and negatively with HLA-DRB1*03 in SLE. (1st June 2022) - Elbagir, Sahwa; Diaz-Gallo, Lina-Marcela; Grosso, Giorgia; Zickert, Agneta; Gunnarsson, Iva; Mahler, Michael; Svenungsson, Elisabet; Rönnelid, Johan
Abstract: Objectives: Emerging evidence demonstrates that aPS-PT associate with thrombotic events. Genetic predisposition, including HLA-DRB1 alleles, is known to contribute to the occurrence of conventional aPL [anti-β2 glycoprotein-I (anti-β2 GPI) and aCL]. We investigated associations between aPS-PT and HLA-DRB1 * alleles and thrombosis in SLE. Conventional aPL were included for comparison. Methods: We included 341 consecutive SLE patients, with information on general cardiovascular risk factors, including blood lipids, LA and thrombotic events. aPS/PT, anti-β2 GPI and aCL of IgA/G/M isotypes and LA were quantified. Results: aPS/PT antibodies associated positively with HLA-DRB1 *13 [odds ratio (OR) 2.7, P = 0.002], whereas anti-β2 GPI and aCL antibodies associated primarily with HLA-DRB1*04 (OR 2.5, P = 0.0005). These associations remained after adjustment for age, gender and other HLA-DRB1 * alleles. HLA-DRB1*13, but not DRB1*04, remained as an independent risk factor for thrombosis and APS after adjustment for aPL and cardiovascular risk factors. The association between DRB1*13 and thrombosis was mediated by aPS-PT positivity . HLA-DRB1*03, on the other hand, associated negatively with thrombotic events as well as all aPL using both uni- and multivariate analyses. HLA-DRB1*03 had a thrombo-protective effect in aPL-positive patients. Additionally, HLA-DRB1*03 was associated with a favourable lipid profile regarding high-density lipoprotein and triglycerides. Conclusions: HLA-DRB1*13 confers risk for both aPS-PT and thrombotic events in lupus. The association between HLA-DRB1*13 and thrombosis is largely, but not totally, mediated through aPS-PT. HLA-DRB1*03 was negatively associated with aPL and positively with favourable lipid levels. Thus, HLA-DRB1*03 seems to identify a subgroup of SLE patients with reduced vascular risk.